Study on the Variations in Physicochemical Property Concentration in a Contaminated Fresh and Salt Water - Ekperi, N.I.; Ozioko F.C; Okirie Faith Uchendu (International Journal of Pollution: Prevention & Control, 2024)
In this research, the dispersion of crude oil contaminated was subjected into laboratory observations and results were recorded. These results were used to develop and adopt mathematical models for a proper engineering experimental practice. 1.5m3 volumes of fresh water and salt water were filled in two tanks of equal fit at the same intervals along the tanks and depth, where samples were collected for the purpose of analysis of physicochemical properties or parameters. The TPH diffusion of the experimented contaminated water environment was examined with the used of mathematical equations on dispersion and degradation combined with first order degradation rate and the Monod equation for both salt and fresh water contaminated water environment. This was observed to have gradual increase with time up to day 56. Then, on the day 70 and 80 respectively, a rapid increase was revealed during the experiment. The effect of crude oil was more in the fresh water compared to salt water media. The TPH predicted by the diffusion model incorporated with first order rate kinetics matched closely with experimental data than the model incorporated with Monod equation. The deviation between the predicted TPH by the model incorporated with Monod equation and the experimental data showed Monod Equation may not be suitable to use as rate parameter in the diffusion model. However, either of the models can be used to study the rate of oil sediment in stagnant water media. The experiment revealed that rate of physicochemical parameters in the contaminated water under investigation was high but was drastically reduced after apply a method known as the bioargumentation technique which helped to accelerate the TPH degradation.
Keywords: Monod Equation; Pollution; Stagnant water; TPH; bioremediation